“It is over there, next to that fat lady”: a qualitative study of fat women’s own body perceptions and weight-related discriminations - Ulian, Mariana Dimitrov; Sato, Priscila de Morais; Pinto, Ana Jéssica; Benatti, Fabiana B.; Campos-Ferraz, Patricia Lopes de; Coelho, Desire; Roble, Odilon J.; Sabatini, Fernanda; Perez, Isabel; Aburad, Luiz; Vessoni, André; Unsain, Ramiro Fernandez; et al. (Saúde e Sociedade, 2020)
We investigated fat women’s perceptions of their own bodies and their experiences with weightrelated discriminations, and how these situations affected their well-being. Thirty-nine obese women were interviewed, and three axes of analysis were identified: (1) repercussions of being fat, (2) living with a fat body, and (3) am I a person or just a fat body? These axes were composed of eight themes which had similar meaning or complemented each other. The results showed our participants had mechanisms to diminish the magnitude of their stigmatized bodies (e.g., attempting to lose weight and changing their current food choices). Participants also reported being fat had physical and psychological consequences for them. Most notably, their larger bodies influenced their self-evaluation, making them feel devalued, unlovable, incapable, and incomplete. They reported stigmatizing experiences in familiar situations, at the workplace and in public spaces, and reported being stigmatized by both close and unknown individuals, including healthcare professionals. These professionals were reported to treat patients disrespectfully, which urges attention to health care inequalities for obese people. Our results stress stigmatizing attitudes towards fat people and their own considerations about themselves have negative consequences in their physical and mental well-being.